Reality and Judgment in the Epistemological Thought of Thomas Aquinas - Hieronymus Simorangkir; Leonard Pasaribu (SEAN Institute, 2023)
Judgment is an intellectual act that arises from the mind's reflection on the process of apprehending reality. This process begins with sensory experience, through which the human intellect recognizes the various relations objectively present in things before it provides rational justification. Through critical reflection, the intellect discloses the rational (noetic) structure of apprehension and thereby understands the correspondence between knowledge and reality. On this basis, judgment, as the second operational act of the intellect, affirms or denies the existence of things and thus establishes the truth of cognition. This study aims to explain the relationship among apprehension, reflection, judgment, and justification as the epistemological foundation of valid knowledge. Employing a qualitative library research approach, the study systematically examines, analyzes, and synthesizes philosophical sources on epistemology that address the concepts of reality and judgment. The data were analyzed using a descriptive-critical method to reconstruct an epistemological synthesis of the formation of valid knowledge. The findings indicate that judgment is preceded by a series of intellectual intuitions that naturally guide the process of reasoning toward justified cognition. Furthermore, universal principles of knowledge are discovered within reality itself; the content of knowledge is grounded in both sensory and intellectual experience; intellectual cognition becomes possible only through the rational understanding of sensory data; and the intellect does not create the content of knowledge but discovers it within concrete reality. Accordingly, the validity of knowledge rests upon the correspondence between the intellect and reality (adequatio intellectus et rei). Through its two fundamental operations apprehension and judgment the human intellect is therefore capable of attaining objective knowledge that is both epistemically valid and philosophically justifiable.